Prognostic implications of double J ureteral stenting in patients with renal stones undergoing extracorporeal shockwave lithotripsy - Jain, Rahul; Raju, Karthikeyan; Bali, Rajandeep Singh; Chander, Jagdish; Neogi, Sushanto (International Journal of Research in Medical Sciences, 2017)
Background: Most patients with uncomplicated kidney stones can be successfully treated with extracorporeal shockwave lithotripsy (ESWL). Double-J ureteral stent is used to facilitate stone clearance, however double-J ureteral stents themselves may cause complications. Study conducted the study to know the exact role of double J stent in ESWL. Methods: 80 patients undergoing ESWL were divided into two groups, group A (n=40) double J stenting and group B (n=40) without double J stenting. Both groups were compared for stone fragmentation, stone clearance, number of shockwaves required for fragmentation, time required for passing through ureter, steinstrasse, Urinary Tract Infection. Results: Both the groups were comparable for age, sex, stone size and stone location distribution. There was no significant difference in clearance of stone and no. of shockwaves received for clearance in both the groups. The overall incidence of steinstrasse between the two groups was insignificant with a p value of 0.644. The incidence of UTI was significantly higher in stented group (p value 0.032). Conclusions: Study recommend ESWL without double J stent in patients having solitary renal calculus of size < 2 cm. Double J stent predisposes the patient to multiple complications including urinary tract infection which increases the morbidity of the patient. Based on our study we conclude that double J stenting in patients of renal calculus of size < 2cm, prior to ESWL is not beneficial.